The effect of perceived organizational support and sense of belonging on teacher empowerment in elementary school teachers - Desi Maria; Jasrial Jasrial; Rusdinal Rusdinal; Merika Setiawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aims to analyze the influence of Perceived Organizational Support and Sense of Belonging on Teacher Empowerment among private elementary school teachers in Padang Utara District, Padang City. A quantitative explanatory research design was employed. The population consisted of 206 teachers, with 135 respondents selected using proportional stratified random sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS 26. The findings indicate that Perceived Organizational Support has a positive but not statistically significant effect on Teacher Empowerment (r = 0.161; R² = 2.6%). In contrast, Sense of Belonging shows a positive and significant effect (r = 0.222; R² = 4.9%). Simultaneously, both variables significantly influence Teacher Empowerment (r = 0.270; R² = 7.3%), although their combined contribution remains relatively low. Sense of Belonging is a more dominant factor in enhancing Teacher Empowerment compared to Perceived Organizational Support. Strengthening teachers’ emotional attachment to the organization is essential for improving empowerment.